If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7f + -12 + f = 20 Reorder the terms: -12 + 7f + f = 20 Combine like terms: 7f + f = 8f -12 + 8f = 20 Solving -12 + 8f = 20 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 8f = 20 + 12 Combine like terms: -12 + 12 = 0 0 + 8f = 20 + 12 8f = 20 + 12 Combine like terms: 20 + 12 = 32 8f = 32 Divide each side by '8'. f = 4 Simplifying f = 4
| x^2-8=-9 | | 4x+3x=28 | | 3(y-2)=4y | | -3x-(5x+1)= | | 3(x-4)+6=5(x+1)+1 | | 7b-5=8b-6 | | 6n-4=n+11 | | 4X^2+1=325 | | 2=1.1+3(m+3) | | 5a=a | | x^2-17x-30= | | 4-0.5k=4 | | 4z-2=20-w | | 7x+6=-57 | | 5(c+4/5)+6=50 | | -3(3y-5x)-y= | | 7a+1=1 | | 5+4(n+9)=3 | | -x+1=13 | | 6=8(s-3/4)-20 | | 3y+6=-3y | | 9*4y=10 | | a-99=176 | | d^2-6d-7= | | x(13-5x)=7 | | (4x+3)-(x-4)=5x+13 | | r-54=29 | | 3(1+9x)=6(2-4x) | | 2p^3-6p^2+15-5p= | | 155+s=249 | | -6-(x-4)=-12 | | 7a^2+35=7-40a |